Detection of Tick-Borne Pathogens in Lambs Undergoing Prophylactic Treatment Against Ticks on Two Swedish Farms - Grandi, Giulio; Aspán, Anna; Pihl, Jenny; Gustafsson, Katarina; Engström, Fredrik; Jinnerot, Tomas; Söderlund, Robert; Chirico, Jan (Frontiers in Veterinary Science, 2018)
Tick-borne pathogens (TBPs), especially Anaplasma phagocytophilum, cause disease in grazing livestock. Tick prophylaxis is therefore a routine practice in sheep flocks in Sweden, especially in central, southern, and coastal areas of the country where ixodid ticks (Ixodes ricinus and Haemaphysalis punctata) are present. In the present study, the status of infection by A. phagocytophilum and other TBPs in lambs treated with tick prophylaxis has been assessed serologically and with PCR. Blood samples (n= 78) from lambs (n=20) subjected to regular tick prophylactic treatment (flumethrin, Bayticol®) at two sites in different regions in Sweden (Östergötland, Gotland) were collected on four occasions from May until July 2013. The severity of clinical signs in Anaplasma infected animals is known to differ between these two regions. In total, 20% of blood samples were PCR-positive for A. phagocytophilum. Serological analyses showed that 33% of all collected samples were positive for A. phagocytophilum, while 2.5% were positive for Borrelia burgdorferi s.l. and 13% for TBEV. Percentages of lambs positive were 75% and 45% for A. phagocytophilum antibodies and DNA, respectively, while 10% and 45% were serologically positive for B. burgdorferi s.l. and TBEV, respectively. Sequencing of partial 16S rRNA genes from Anaplasma PCR positive samples revealed presence of A. phagocytophilum in all animals in Östergötland, while sequences consistent with A. phagocytophilum as well as A. capra and A. bovis were found on the island of Gotland. This is the first report of the occurrence of the latter two species in Sweden.